2021
DOI: 10.1177/0363546520985184
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical, Cadaveric Evaluation of Single- Versus Double-Row Repair Techniques on Stability of Bony Bankart Lesions

Abstract: Background: Previous studies comparing stability between single- and double-row arthroscopic bony Bankart repair techniques focused only on the measurements of tensile forces on the bony fragment without re-creating a more physiologic testing environment. Purpose: To compare dynamic stability and displacement between single- and double-row arthroscopic repair techniques for acute bony Bankart lesions in a concavity-compression cadaveric model simulating physiologic conditions. Study Design: Controlled laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Conversely, some authors have reported that Bankart repair using a double-row repair technique is reliably efective for shoulder instability [11][12][13][14]. Cadaveric studies have shown that double-row capsulolabral repair might restore normal anatomy more efectively than single-row repair [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, some authors have reported that Bankart repair using a double-row repair technique is reliably efective for shoulder instability [11][12][13][14]. Cadaveric studies have shown that double-row capsulolabral repair might restore normal anatomy more efectively than single-row repair [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Small defects can be treated well with an arthroscopic Bankart repair, whereas significant bone defects lead to a recurrence rate of up to 67% when treated with a soft tissue reconstruction alone [3]. A bone loss of 20–25% relative to the glenoid extent of the short axis, hereinafter referred to as defect width, is a widely accepted threshold at which bony reconstruction is preferred over soft tissue Bankart repair [6, 8, 16, 29]. However, current studies and clinical outcomes recommend lower thresholds to indicate subcritical or minor bone loss [11, 24, 25, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Millett et al introduced their "bony Bankart bridge" technique in 2009, which allows a double-point fixation of the bony fragment to elude the drawbacks of a single-point fixation [16], and reported durable clinical improvement in clinical outcomes and high return-to-sport rate at a minimum 5-year follow-up [23]. Biomechanical studies were able to demonstrate an improved fracture reduction and stability of the bony fragment using a doublerow bridge reconstruction compared to single row [19,20,21]. In addition, a variety of further double-row reconstruction techniques have been described in the literature [12,14,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been our experience that with this technique, it is difficult to maintain fragment reduction, as the medial support is lacking and the fragment tends to invert, thus creating a step-off in the articular surface. Although arthroscopic linked double-row fixation allows for better fracture reduction and stability compared to single-row fixation methods [19,20,21], these techniques are increasingly complex and rely on permanent sutures passing over the articular surface of the fractured fragment, which may cause degeneration of the articular cartilage over time. The purpose of this report was to introduce an arthroscopic independent doublerow (IDR) bony Bankart repair technique for fixation of large glenoid fractures (▶ Fig.…”
Section: Introductionmentioning
confidence: 99%